AUDITING AND ACCOUNTING SYSTEMS: A MARRIAGE PROPOSAL. - Stettler, Howard F. (The Accounting Review, 1964)
Abstract It might seem that auditing and accounting systems would be relatively unsuited for marriage, but consider these points of compatibility that suggest the possibility of wedded bliss. Firstly, both subjects are peripheral to the central core of accounting theory and practice. Secondly, the study of auditing presently includes, in most instances, the question of internal control, which is a key aspect in the consideration of accounting systems. Thirdly, auditing involves in large measure the audit of the accounting system that produces the figures that appear in the financial statements. Fourthly, the concept of constructive auditing is especially dependent on a knowledge of accounting systems and management advisory services that frequently result from constructive auditing recommendations similarly require a knowledge of accounting systems. Fifthly, audit trial considerations are a part in the design of accounting systems. The study of both these subjects can be covered together in less time than they can be covered separately.